New shape function solutions for fracture mechanics analysis of offshore wind turbine monopile foundations - Bocher, Mathieu; Mehmanparast, Ali; Braithwaite, Jarryd; Shafiee, Mahmood (Elsevier, 2018)
Offshore wind turbines are considered one of the most promising solutions to provide sustainable energy. The dominant majority of all installed offshore wind turbines are fixed to the seabed using monopile foundations. To predict the lifetime of these structures, reliable values for shape function and stress intensity factor are needed. In this study, a new equation is developed through finite element simulations which have been performed for a wide range of monopile geometries with different dimensions, crack lengths and depths, to evaluate shape function and stress intensity factor solutions for monopiles. The new solutions have been verified through comparison with the existing solutions provided by Newman & Raju for small hollow cylinders. The empirical shape function solutions developed in this study are employed in a case study and the results have been compared with the existing shape function solutions. It is found that the old solutions provide inaccurate estimations of fatigue crack growth in monopiles and they underestimate or overestimate the fatigue life depending on the shape function solution employed in the structural integrity assessment. The use of the new solution will result in more accurate monopile designs as well as life predictions of existing monopile structures.
Keywords: Stress intensity factor; Shape function; Fatigue crack growth; Inspection; Monopile; Offshore wind turbine